Exchange Rate Fundamentals and Dynamics in a Liberalized Foreign Exchange Market: Evidence from Uganda - Opolot, Jacob; Anguyo, Francis Leni (Bank of Uganda Staff Papers Journal., 2007)
This paper investigates exchange rate fundamentals and dynamics since the liberalization of the foreign exchange market in Uganda. The longrun behaviour of the exchange rate and the underlying fundamentals is investigated using both multivariate cointegration framework and dynamic ordinary least squares (DOLS). The DOLS elasticities are largely consistent with those derived from the Johansen and Juselius maximum likelihood approach, except in a few cases. In general both approaches indicate that the fundamentals determine the longrun behaviour of the exchange rate in Uganda are domestic money supply, price differential, terms of trade, and private transfers or remittances from abroad. Having established the existence of a long run relationship, the shortrun dynamics are investigated using a vector error correction model. The results indicates that 2.7 percent of the adjustment towards the longrun equilibrium takes place in one month. In terms of shortrun dynamics, the significant lags are a one-period and a two-period lagged difference of the exchange rate; a two-period and a three-period lagged difference of money supply; a oneperiod, two-period and three-period lagged difference of the price differential; a two period lagged difference of the terms of trade; a one-period and four-period lagged difference of private transfers; and a two-period lagged difference of the foreign interest rate. It is thus evident that the exchange rate behaviour is influenced by monetary policy actions, current account dynamics, and to a limited extent, movements in foreign interest rates
Keywords: Exchange rate, Exchange rate fundamentals and dynamics, cointegration, dynamic ordinary least squares, vector error correction model.